ERROR ANALYSIS OF SHORT STORY BASED ON SURFACE STRATEGY TAXONOMY OF FIRST GRADE SENIOR HIGH SCHOOL IN SMAN 1 TUAL - Ida Rafda Raubun; Badruddin Kaddas; Muthmainnah Mursidin (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The purpose of this research was to find out surface structure errors in writing short stories made by students of the first grade in SMA Negeri 1 Tual and to find out the most mistakes made by students of SMA Negeri 1 Tual based on surface strategy taxonomy. The method used in this research is the descriptive qualitative method. This research sample consists of 25 students in one class. One instrument used in this research was the essay test. In the collecting data, the researcher identified 25 short stories from twenty-five students who came from one class in the tenth grade of SMAN 1 Tual to complete the data. As a result of this research, 306 errors had occurred in the 25 short stories. It was found that superficial errors and omissions made up of the error numbers, addition made up 24%, misformation made up 31%, and misordering was 3%. The most dominant error was omission with a total of 128 errors or 42% errors made by students. The total incorrect error was 306. It consisted of four types of errors, namely 128 errors or 42% of omissions, 96 errors or 31% of misformation, 73 errors or 24% of additions and the last 9 errors or 3% misordering.